Examining dual-factor mental health: a confirmatory factor analysis among senior secondary students in Islamic boarding schools - Rahmat Aziz; Esa Nur Wahyuni; Wildana Wargadinata; Ali Maksum; Retno Mangestuti; Iffat Maimunah (Institute of Advanced Engineering and Science, 2026)
This study examines the measurement properties of the dual-factor model of mental health among senior secondary students in Islamic boarding schools. Despite growing interest in the dual-factor framework, empirical validation in culturally embedded educational settings remains limited. Using a quantitative cross-sectional design, data were collected from 616 students across 10 schools using the Azira Mental Health Scale (AMHS-24), which assesses psychological well-being and psychological distress. Confirmatory factor analysis (CFA) supported a two-factor structure, indicating that well-being and distress are distinct yet related constructs. The model showed acceptable but not optimal fit (root mean square error of approximation (RMSEA)=.055; standardized root mean square residual (SRMR)=.063; comparative fit index (CFI)=.874; Tucker–Lewis index (TLI)=.862). Reliability was satisfactory (α=.855 and .861), and discriminant validity was supported (heterotrait–monotrait (HTMT)=.321). However, convergent validity was limited (average variance extracted (AVE)=.332 and .343). The novelty of this study lies in validating a dual-factor mental health instrument within Islamic boarding schools, providing a contextually grounded assessment of both positive and negative dimensions. Despite this limitation, the findings support the use of the AMHS-24 as a reliable tool for assessing general mental health patterns.